Rude Awakening: Social and Media Change in Central And Eastern Europe - Jakubowicz, Karol (Javnost-The Public, 2001)
This article reviews the transformation in society and the media in the former communist countries of central and eastern Europe. Adopting a `path dependence approach', the different countries of the region are analysed and allocated to two general categories, depending upon the nature and extent of the changes that have taken place in society and the media. The first group of countries (called here `Type A') have advanced relatively far along the road to transformation. Examples would be Poland, the Czech Republic, Hungary, Slovenia, Estonia. The second group (called here `Type B') retain much more of the old order. Examples would be Russia and some of the other republics that have issued from the collapse of the old Soviet Union. A range of theories of media change are reviewed, and their prognoses for the development of the media after the fall of communism are tested against the subsequent developments. It is argued that the media in both Type A and Type B countries remain highly politicised, particularly in the case of broadcasting, and with limited independence from the political elite. Journalism, too, remains paternal and didactic, partly as a result of the historical position of intellectuals in the region. While there are important differences between Type A and Type B countries, neither represents a stable and finished model of transformation. In neither case, are the media the passive victims of social forces. On the contrary, their shortcomings help to reproduce the limits of the overall transformation process.